A COMPARATIVE ANALYSIS OF THE FINANCIAL COSTS FOR ACCESSING THE SAME BASIC KINESIS-THERAPEUTIC SERVICE AVAILABLE TO THE POPULATION FROM DIFFERENT PARTS OF THE EUROPEAN UNION - Alexe Dan Iulian; Deleu Cristina (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2014)
Discriminating the type of ratio between a basic kinesis-therapeutic service available to the population and its corresponding costs in different EU areas. Performing a comparative analysis of the costs for different types of massage for the European market for the relaxation-recovery services can offer new data and reference points to future specialists in these areas when they plan and design their access on such a competitive market. Knowledge of the massage services, of the national economic characteristic, of the principles governing the recovery-rehabilitation -relaxation activities in every EU country can reveal real and positive evidences for the professional career orientation, but also regarding the massage service appreciation within such a large market, as the European Union's. For the same type of basic kinesis-therapeutic service available to the population (massage), establishing extreme limits for the corresponding costs can represent a challenge difficult to accomplish at the level of EU areas, and this aspect shows, in our opinion, a lack of financial stability and "standardization" of the services for which a kinesiotherapist is trained and specialized.